If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5) = (x + 21) Reorder the terms: (-5 + 3x) = (x + 21) Remove parenthesis around (-5 + 3x) -5 + 3x = (x + 21) Reorder the terms: -5 + 3x = (21 + x) Remove parenthesis around (21 + x) -5 + 3x = 21 + x Solving -5 + 3x = 21 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 3x + -1x = 21 + x + -1x Combine like terms: 3x + -1x = 2x -5 + 2x = 21 + x + -1x Combine like terms: x + -1x = 0 -5 + 2x = 21 + 0 -5 + 2x = 21 Add '5' to each side of the equation. -5 + 5 + 2x = 21 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 21 + 5 2x = 21 + 5 Combine like terms: 21 + 5 = 26 2x = 26 Divide each side by '2'. x = 13 Simplifying x = 13
| 12R^2=R+20 | | 2(4x-3)+7=3x+8 | | 7x-30=15 | | =(2x-4)+6 | | 3x-3(2x-8)=3(3x-7)+5x | | 8(t+2)-3y(t-4)=6(t-7)+8 | | -2(n-5)-(3n-1)=-6+(2n-1) | | h(t)=-16t+32t | | -5-10=15 | | Y=2x+16-9 | | =(3x-1)-(3x-1) | | h=vt+16t^2-hforv | | -2b+-4= | | n+6+7=-5+4n | | (3x+10)=(6x-10) | | 3n+2n+n= | | =(x-2)(x-5) | | 1+b=-1+2b | | 4x-6=2x-6 | | 3x+15+3y=x+10 | | b+-2b+-4= | | 21=9+3 | | 3(3x+7)=48 | | 21=9+3x | | (-6p)+(-6p)=-112 | | -14-7x=-8x-8 | | (4x+2)=(6x-30) | | 7a+4m+7= | | 6-x+2=-3 | | Y=21x+98 | | 6-6a=-6-5a+5 | | 7/3x+2/5= |